Reversing the Extraverted Leadership Advantage: The Role of Employee Proactivity - Grant, Adam M.; Gino, Francesca; Hofmann, David A. (Academy of Management Journal, 2011)
Extraversion predicts leadership emergence and effectiveness, but do groups perform more effectively under extraverted leadership? Drawing on dominance complementarity theory, we propose that although extraverted leadership enhances group performance when employees are passive, this effect reverses when employees are proactive, because extraverted leaders are less receptive to proactivity. In Study 1, pizza stores with leaders rated high (low) in extraversion achieved higher profits when employees were passive (proactive). Study 2 constructively replicates these findings in the laboratory: passive (proactive) groups achieved higher performance when leaders acted high (low) in extraversion. We discuss theoretical and practical implications for leadership and proactivity.